Crosstalk Between Histone and m6A Modifications and Emerging Roles of m6A RNA Methylation - Xu, Zibin; Xie, Tingfei; Sui, Xiaolu; Xu, Yunpeng; Ji, Lecai; Zhang, Yanzi; Zhang, Aisha; Chen, Jihong (Frontiers in Genetics, 2022)
RNA, like DNA and proteins, has been discovered to undergo dynamic and reversible chemical alterations, increasing the diversity and functional complexity of the molecule. N-6-methyladenosine (m6A) RNA methylation serves as a bridge between transcription and translation and is critical for many diseases' progression. There is a complex interrelationship between m6A modifications and other epigenetic modifications. Their crosstalk significantly affects transcriptional outputs, translation, recruitment of chromatin modifiers, as well as the deployment of the m6A methyltransferase complex at target sites. This article outlines the potential function of m6A RNA methylation in epigenetics and summarizes its interactions with histone modifications.